Unzipping of functionalized multiwall carbon nanotubes Induced by STM - Paiva, M. C. (2010)
Carbon nanotubes (CNTs), functionalized by a cycloaddition reaction, were studied by ultrahigh vacuum scanning tunneling microscopy (STM). The STM images provided evidence for partial or total unzipping of the outer CNT layer. The formation of graphene ribbons was triggered by the STM tip, under specific operating conditions. A model for the unzipping is proposed, based on the perturbation of the π-conjugation along the CNT surface induced by the cycloaddition reaction.